1987
DOI: 10.1111/j.1749-6632.1987.tb35835.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation, Imagery, and Neuroimmunomodulationa

Abstract: Thirty undergraduates screened for high absorption ability were randomly assigned to three conditions. The first condition consisted of relaxation alone (progressive muscle relaxation and focused breathing). The second one combined this same relaxation training with mental imagery of the immune system. The third condition served as an alertness or mild arousal control; in a vigilance task subjects discriminated between tones presented in variable inter-trial intervals. Subjects reported trial levels of tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…These interventions presumably reduce subjective distress and physiological arousal. Only two studies included neuroendocrine assessments (Green and Green, 1987; lasnoski and Kugler, 1987), and both studies reported that there was no change in these measures following the intervention. Surprisingly, of the three studies (Green et al, 1988;Groer et al, 1994) that assessed psychological distress, only one study ) observed a decrease in psychological distress after the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These interventions presumably reduce subjective distress and physiological arousal. Only two studies included neuroendocrine assessments (Green and Green, 1987; lasnoski and Kugler, 1987), and both studies reported that there was no change in these measures following the intervention. Surprisingly, of the three studies (Green et al, 1988;Groer et al, 1994) that assessed psychological distress, only one study ) observed a decrease in psychological distress after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that stress can affect the immune system, including s-IgA, raises the possibility that positive experiences, the opposite of stressful ones, could also affect the activity of the immune system (jasnoski and Kugler, 1987;Zakowski et al, 1989;Van Rood et al, 1993).…”
Section: Relaxation and Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…No clear association between the alterations of HPA hormone measures which have been described in depressed subjects and immune status has been reported. Jasnosky and Kugler [78] demonstrated that patients doing relaxation and imagery had higher levels of serum IgA, with a negative relationship between IgA and plasma norepinephrine levels. This evidence supports that a systemic response may integrate the biochemical, metabolic, neural, and hormonal events after a behavioral intervention [78].…”
Section: Psychoimmune Interactionsmentioning
confidence: 99%
“…The treatment group initially showed a decrease in white blood cell count but then displayed a significant increase over time as participants became more relaxed and in control of their imagery. Healing imagery has been found to physically boost immune system function as displayed through increased activation of helper T cells (Jasnowski & Kugler, 1987) as well as through increased production m-IgA in the saliva (Gregson, Roberts, & Amiri, 1996).…”
mentioning
confidence: 99%